Fixed and Mobile Phoning in Italian Regions - Domenico Campisi; Roberta Costa; Carlo Tesauro (European Regional Science Association (ERSA), 2003)
The telecommunication diffusion and it's interaction with the socio-economic environment was analysed both in terms of introduction of new technologies in the market and their diffusion/substitution process with respect to former technologies. Nevertheless, the word ?innovation? should be referred to products in a more general sense, so avoiding limitations to technology but also keeping track of all those characterising elements of products inside the market. Due to a similar approach, should be considered as innovative a product even if it doesn?t contain technological components different with respect to pre-existing ones, but also if a former technology is sold using totally innovative formulas. This modified viewpoint requires a more flexible approach to the diffusion process. This approach can enhance the interest on studying those different answers adopted by different socio-economic environments, to analyse the characteristic elements enabling the identification of categories with similar behaviour. Keywords: Telecommunications, Innovation, Diffusion, Clustering
Keywords: 330